Performance of soy cultivars in the south of Minas Gerais State, Brazil - Batista, Elaine Cristina; Pereira, José Luiz de Andrade Rezende; Bruzi, Adriano Teodoro; Zambiazzi, Everton Vinucius; Silva, Karina Barroso (Revista Agrogeoambiental, 2017)
Cultivar evaluation is one of the basic steps recommended for a given region, since the best adapted cultivars have higher yields, and success in this parameter is based on the genotype of the material and its interaction with the environmental variables. The aim of this study was to evaluate the behavior of 23 soy cultivars in the soil-climatic conditions of the south region of Minas Gerais State (MG), Brazil, in the municipality of Inconfidentes. The evaluated traits were grain yield, plant height, height of insertion of the first legume and lodging. The experiments were conducted on the 2013/2014 and 2014/2015 harvests, adopting a randomized block design with three replicates and 23 treatments, which were constituted by the following cultivars: FAVORITA RR, BRS MG 760SRR, NA 5909 RG, NA 7200 RR, CD 2630, CD 250, NA 7620 RR, CD 2737, TMG 123, V-MAX RR, P 98Y11 RR, NS 7100 RR, BMX Potencia, Anta 82 RR, CD 237, V-TOP, TMG 1176 RR, TMG 1174 RR, TMG 1179 RR, TMG 1181 RR, BMX Força, Monsoy 7211 RR and BRS MG 780 RR. Of the studied cultivars, those that most stood out for the traits evaluated in the conditions of Inconfidentes (MG) were TMG 1179 RR (48.6 bags of 60 kg ha-1), NA 7200 RR (45.6 bags), CD 2737 (41.1 bags), CD 237 (41 bags) and BRS MG 760 SRR (40.6 bags), all of which displayed satisfactory conditions for mechanical harvesting, demonstrating the good performance of the crop in the south region of Minas Gerais State.